Theoretical design of stable hydride clusters: isoelectronic transformation in the EnAl4−nH7+n− series. Issue 26 (14th March 2017) - Giraldo, Carolina; Ferraro, Franklin; Hadad, C. Z.; Riuz, Lina; Tiznado, William; Osorio, Edison
Abstract : Design of stable hydrogen-rich metallic hydrides through substitutions of one aluminum atom by one E–H unit in the Al4 H7 − cluster (E = Be, Mg, Ca, Sr and Ba atoms). Abstract : New stable hydrogen-rich metallic hydrides are designed by systematic transformations of the stable known Al4 H7 − species, carried out by successive isoelectronic substitutions of one aluminum atom by one E–H unit at a time (where E = Be, Mg, Ca, Sr and Ba atoms). Searches on the potential energy surfaces (PESs) of EAl3 H8 −, E2 Al2 H9 −, E3 AlH10 − and E4 H11 − systems indicate that structural analogues of Al4 H7 − become higher energy isomers as the number of E–H units increases. The electronic descriptors: Vertical Electron Affinity (VEA), Vertical Ionization Potential (VIP) and the HOMO–LUMO gap, suggest that the systems composed of EAl3 H8 −, E2 Al2 H9 −, E3 AlH10 −, with E = Be and Mg, would be the most stable clusters. Additionally, for a practical application, we found that the Be–H and Mg–H substitutions increase the hydrogen weight percentage (wt%) in the clusters, compared with the isoelectronic analogue Al4 H7 − . The good capacity of beryllium and magnesium to stabilize the extra hydrogen atoms is supported by the increment of the bridge-like E–H–Al, 3center–2electron chemical bonds. Finally, explorations on the PESs of the neutral species (using Na + as counterion) indicate that the NaBe2 Al2 H9, NaBe3 AlH10 and NaMg3 AlH10 minimum-energy structures retain the original geometric shapes of the anionic systems. This analysis supports the potential use of these species as building blocks for cluster-assembled hydrides in the gas phase.